SPECIFIC DISORDERS OF THE RESPIRATORY SYSTEM IN CYSTIC FIBROSIS. CLINICAL EFFICACY OF THERAPY WITH DORNASE ALFA IN CHILDREN - T.V. Simanova; A.M. Ozhegov; A.V. Tsyganok (Педиатрическая фармакология)
The article is devoted to specific disorders of the respiratory system in cystic fibrosis. 64 patients with cystic fibrosis (CF) aged 2 months to 32 years and residing in the Udmurtian Republic were studied. Epidemiological and genetic specifics of this disease in the mentioned region of the RF were examined. Clinical, X-ray, functional and microbiological studies of the CF patients’ respiratory system were conducted. It was found that genotype delF508 and chronic infection Pseudomonas aeruginosa, Staphylococcus aureus cause severe structural changes to the bronchopulmonary system more often. The obtained data suggest the advisability of identifying the groups of CF patients at the highest risk of severe respiratory system disorders in order to optimise therapeutic efforts. The article provides indicators of clinical efficacy of a dornase alfa therapy in CF children.Key words: cystic fibrosis, genotype, delF508 mutation, respiratory organs, pseudomonas aeruginosa infection, staphylococcal infection, respiratory function, mucolytic function, dornase alfa. (Pediatric Pharmacology. – 2010; 7(6):44-48)